Absolute reliability of adipose tissue volume measurement by computed tomography: application of low-dose scan and minimal detectable change—a phantom study - Onuma, Takahiro; Kamishima, Tamotsu; Sasaki, Tsukasa; Sakata, Motomichi (Radiological Physics and Technology, 2015)
Metabolic syndrome increases the risk of developing diabetes and cardiovascular disease, particularly heart failure. Abdominal obesity is commonly assessed by measurement of the waist circumference, which exhibits a positive correlation with the visceral fat area measured on computed tomography (CT). CT is an excellent technique for measurement of cross-sectional areas of adipose tissue, but the exposure to ionizing radiation limits broad and repeated application in healthy subjects. Our purpose in this study was to determine the reliability of low-dose CT for abdominal fat quantification as compared with a standard CT protocol. A phantom was scanned by use of changes in the volume of vegetable oil, simulating visceral and subcutaneous adipose tissue, and by changes in the tube current–time products (25–300 mAs). We measured the volume of vegetable oil for each mAs value, and we calculated the minimal detectable change (MDC) in the volume by making repeated measurements. The measured volume of vegetable oil at 50 mAs and higher was not significantly different ( p > 0.05), but that at 25 mAs was significantly different ( p < 0.001), from that at 300 mAs. The MDC was less than 0.4 ml regardless of the mAs value at all mAs values assessed. We suggest that the adipose tissue volume is determined accurately by CT at 50 mAs (75 % reduction of radiation exposure compared with the standard dose).